Modern international economics : a balance of payments approach - Wasserman, Max Judd; Hultman, Charles W. (New York : Simmons-Boardman Pub. Corp., 1962)
This book deals with the background of international economics and it's historical sketch
Includes bibliography.
oo 15/10/18
Loans
Keywords: International economic relations